Forestry and Water Conservation in South Africa - Bennett, Brett (ANU Press, 2015)
This innovative interdisciplinary study focuses on the history, science, and policy of tree planting and water conservation in South Africa. South Africa's forestry sector has sat-often controversially-at the crossroads of policy and scientific debates regarding water conservation, economic development, and biodiversity protection. Bennett and Kruger show how debates about the hydrological impact of exotic tree planting in South Africa shaped the development of modern scientific ideas and state policies relating to timber plantations, water conservation, invasive species control, and biodiversity management within South Africa as well as elsewhere in the world. Forestry and Water Conservation in South Africa shows how scientific research on the impact of exotic and native vegetation led to the development of a comprehensive national policy for conserving water, producing timber, and protecting indigenous species from invasive alien plants. Policies and laws relating to forests and water began to change in the late 1980s and early 1990s as a result of political and administrative changes within South Africa. This book suggests that the country's contemporary policies towards timber plantations, guided by the National Water Act of 1998, need to be reconsidered in light of the authors' findings. Bennett and Kruger also call for more interdisciplinary research and greater emphasis on integrated policies and management plans for forestry, invasive alien plants, water conservation, and biodiversity preservation.